Ups and downs in English language teacher education in Hungary in the last half century - Kontra, Miklós (Working Papers in Language Pedagogy, 2016)
This paper will NOT address the catastrophic effects of the government-imposed structural changes to Hungarian teacher education since 1990, nor will it concern itself with the low quality of life our teachers face, or how English linguistic and cultural imperialism is resisted or enhanced by our teacher training programs. Instead, I will demonstrate how our Humboldtian/neohumanist tradition of teacher education dating back to 1872 has dominated English language teacher training even in the last fifty years, and will give a criticism of the snobbery in our academic life which deems educational linguists’ and language educators’ work “unacademic” and looked down upon. The traditional teacher education model was significantly challenged when, in addition to the double major[1] 5-year teacher education programs, 3-year single major programs were started in 1990, with considerable help from the World Bank, the British Council, USIS and Peace Corps. These new programs focused on language pedagogy and practical teacher education, and provided considerably increased teaching practice. Similarly to the Netherlands in the 1970s, this was “an uphill fight against tradition, vested interests and mental inertia” (van Essen, 1996, p. 21). The quality of the programs was internationally recognized and the Centers for English Teacher Training (CETTs) became a model for restructuring English teacher education in Central Europe. The 1990s saw the all-time peak of English teacher education in Hungary. After 1997 the CETTs were forcibly (re)merged with the traditional philology departments (aka Departments of English Studies), and a lot of their achievements were wasted. The quality of teacher education seems to be under serious threat again and the academic prestige of teacher educators continues to be minimal, despite the international fame of some Hungarian applied linguists and teacher educators, and the high-quality MA and PhD programs they direct. In conclusion, I will offer my ideas on what could be done in this situation, which is aggravated by chaotic educational language policy decisions from our governments and the curse of the age-old SCHOLARLY teacher vs. PRACTICE ORIENTED teacher controversy in our (English) teacher education.